Stroke thrombolysis in England, Wales and Northern Ireland: how much do we do and how much do we need?. Issue 1 (25th June 2010) - Rudd, A G; Hoffman, A; Grant, R; Campbell, J T; Lowe, D
Abstract : Background: Data are limited on the proportion of stroke patients nationally appropriate for thrombolysis either within the 3 h time window or the recently tested 4.5 h. This information is important for the redesign of services. Methods: Data on case mix, eligibility for thrombolysis, treatment and outcomes were extracted from the National Sentinel Stroke 2008 Audit dataset. This contains retrospective data on up to 60 consecutive stroke admissions from each acute hospital in England, Wales and Northern Ireland between 1 April and 30 June 2008. Findings: All relevant hospitals participated, submitting data on 11 262 acute stroke patients. 2118 patients arrived within 2 h and 2596 within 3 h of the onset of symptoms and 587 people were already in hospital. Therefore, 28% (3183) were potentially eligible for thrombolysis based on a 3 h time criterion. Of these, 1914 were under 80 years and 2632 had infarction with 14% (1605) meeting all three National Institute of Neurological Disorders and Stroke study criteria and so being potentially eligible for thrombolysis. If the time window is increased to 4.5 h then only another 2% became eligible. If the age limit was removed for treatment, the percentage potentially appropriate for tissue plasminogen activator increased to 23% within 3 h and 26% within 4.5 h. Overall, 1.4% (160) of patients were thrombolysed. Interpretation: Thrombolysis rates are currently low in the UK. 14% of patients in this sample were potentially suitable for thrombolysis using the 3 h time window. This would only increase marginally if thrombolysis was extended to include those up to 4.5 h. The greatest impact on increasing the proportion of patients suitable for thrombolysis would be to increase the number of patients presenting early and by demonstrating that the treatment is safe and effective in patients over 80 years of age.